Homework Help

Let f (x)= (3x+1) Calculate  A) 2f(0)+f(-2) B) f (0)f(-2)

user profile pic

user770979 | eNotes Newbie

Posted May 18, 2013 at 4:45 AM via web

dislike 1 like

Let f (x)= (3x+1)

Calculate 

A) 2f(0)+f(-2)

B) f (0)f(-2)

1 Answer | Add Yours

user profile pic

crmhaske | College Teacher | (Level 3) Associate Educator

Posted May 18, 2013 at 4:51 AM (Answer #1)

dislike 1 like

In order to solve this question you must substitute each value of x into the equation and solve for f(x):

`f(0)=3(0)+1=1`
`f(-2)=3(-2)+1=-5`

Therefore:

`2f(0)+f(-2)=2(1)+(-5)=-3`

And:

`f(0)f(-2)=(1)(-5)=-5`

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes